The Civil War [videorecording (Blu-Ray)] - McCullough, David G.; Ward, Geoffrey C.; Dewhurst, Colleen; Fishburne, Laurence, III, 1961-; Freeman, Morgan; Irons, Jeremy, 1948-; Jacobi, Derek; Robards, Jason; Waterston, Sam; Axton, Hoyt; Shaw, Bruce (Ken Burns., 2015)
Ken Burns' Emmy Award-winning epic documentary, digitally enhanced, features never-before-seen interviews, commentary from Ken Burns, a sixteen-page collector's booklet and more. It tells the story of a country that had to divide itself in two in order to become one.